A Homolog of Structural Maintenance of Chromosome 1 Is a Persistent Centromeric Protein Which Associates With Nuclear Pore Components in Toxoplasma gondii - Francia, Maria E.; Bhavsar, Sheila; Ting, Li-Min; Croken, Matthew M.; Kim, Kami; Dubremetz, Jean-Francois; Striepen, Boris (Frontiers in Cellular and Infection Microbiology, 2020)
Apicomplexa are obligate intracellular parasites which cause various animal and human diseases including malaria, toxoplasmosis, and cryptosporidiosis. They proliferate by a unique mechanism that combines physically separated semi-closed mitosis of the nucleus and assembly of daughter cells by internal budding. Mitosis occurs in the presence of a nuclear envelope and with little appreciable chromatin condensation. A long standing question in the field has been how parasites keep track of their uncondensed chromatin chromosomes throughout their development, and hence secure proper chromosome segregation during division. Past work demonstrated that the centromeres, the region of kinetochore assembly at chromosomes, of Toxoplasma gondii remain clustered at a defined region of the nuclear periphery proximal to the main microtubule organizing center of the cell, the centrosome. We have proposed that this mechanism is likely involved in the process. Here we set out to identify underlying molecular players involved in centromere clustering. Through pharmacological treatment and structural analysis we show that centromere clustering is not mediated by persistent microtubules of the mitotic spindle. We identify the chromatin binding factor a homolog of structural maintenance of chromosomes 1 (SMC1). Additionally, we show that both TgSMC1, and a centromeric histone, interact with TgExportin1, a predicted soluble component of the nuclear pore complex. Our results suggest that the nuclear envelope, and in particular the nuclear pore complex may play a role in positioning centromeres in T. gondii.